Analysis of odontoid parameters in adolescent idiopathic scoliosis patients with different curve types - Li, Kelin; Huang, Longao; Xiao, Qiongrun; Chen, Weiyou; Du, Yuwang; Jiang, Hua (Frontiers in Pediatrics, 2024)
Introduction: Odontoid incidence (OI) is an important parameter that has recently been developed. However, there are currently no studies on OI in adolescent idiopathic scoliosis (AIS) patients. We aimed to examine the significance of OI in describing cervical sagittal alignment in AIS patients, explore the differences in cervical sagittal parameters among these patients with different curve types, and investigate the correlations between coronal deformity and cervical sagittal parameters in AIS patients. Methods: The whole-spine anteroposterior and lateral plain radiographs of AIS patients were retrospectively analyzed. The parameters, including OI, odontoid tilt (OT), C2 slope, cervical lordosis (CL), T1 slope (T1S), and others, were measured. The AIS patients were grouped based on different curve types. Measurement parameters were compared between different groups. Pearson correlation analysis was performed for cervical sagittal parameters and Cobb angle. Results: Ninety AIS patients were included, consisting of 14 males and 76 females. The main thoracic curve group exhibited a smaller OI compared to the main thoracolumbar/lumbar curve group (P < 0.05). In the AIS patients with a main thoracic curve, there was a significant correlation between Cobb angle and OI (r = −0.371, p < 0.01). The odontoid parameters exhibited significant correlations with several classic cervical sagittal parameters in AIS patients with different curve types. The validation of the formula CL = 0.36 × OI − 0.67 × OT − 0.69 × T1S showed a significant correlation (correlation coefficient = 0.917) between the actual measurements and the predicted values, with a determination coefficient of 0.842. Conclusion: There may be a difference in OI between AIS patients with a main thoracic curve and those with a main thoracolumbar/lumbar curve. Odontoid parameters could be used to describe cervical sagittal alignment in AIS patients with different curve types.